Shelter interventions prevent and mitigate displacement - Wadley, D (Refugee Studies Centre, University of Oxford, 2012)
In hazard-prone developing countries, shelter interventions are an important way to prevent or mitigate natural disaster-induced displacement. To be effective, however, they need to be multi-faceted and carried out with the involvement of the communities affected.